AB0172 Protection from articular damage by passive or active anti-TNF alpha immunotherapy in human-TNF alpha transgenic mice depends on anti-TNF alpha antibody levels. (23rd January 2014) - Semerano, L.; Biton, J.; Delavallee, L.; Duvallet, E.; Assier, E.; Bessis, N.; Bernier, E.; Dhellin, O.; Grouard-Vogel, G.; Boissier, M.-C.
Abstract : Background: In human TNFα (hTNFα) transgenic mice (TTg), active anti-TNFα immunization with the kinoid of TNFα (TNF-K) induces polyclonal anti-hTNFα antibodies and results in amelioration of arthritis 1, 2, 3 Objectives: 1) To compare the efficacy of TNF-K to that of infliximab (IFX) and to that of TNF-K and IFX co-administration. 2) To evaluate whether the titers of anti-hTNFα antibodies (Ab) induced by active immunization are a determinant of TNF-K efficacy. Methods: Forty-eight TTg mice received one of the following treatments: TNF-K immunization (TNFK group); weekly IFX all along study duration (IFXw0-15); TNF-K plus weekly IFX for 4 weeks (TNF-K+IFX), weekly IFX for 4 weeks (IFXw0-4); PBS. Animals were sacrificed at week 16. Anti-hTNFα Ab titers IFX serum levels and clinical and histological scores were compared. Results: All TNF-K immunized mice (TNF-K and TNF-K+IFX) produced anti-hTNFα Ab. Ab titers were higher in the TNF-K group vs. TNF-K+IFX (p<0.001) and inversely correlated to histological inflammation (R=-0.78; p=0.0001) and destruction (R= -0.67; p=0.001). Mice with high vs. low anti-hTNFα Ab titers had less histological inflammation and destruction (p<0.05). Similarly, the serum levels of infliximab in IFX-only treated mice showed inverse correlation with histological inflammation (R= - 0.56; p<0.05) and destruction scores (R -0.57; p<0.05). TNF-K and long-term IFX treatment (IFXw0-15) didn't differ in clinical and histological amelioration of arthritis. The group that received TNF-K and IFX co-administration (TNF-K+IFX) had a more rapid clinical improvement (p<0.05) but higher histological inflammation and destruction (p<0.05) compared to the group that received solely TNF-K. Conclusions: In a model of TNFα–dependent arthritis, protection from articular damage by TNF-K correlates with the titers anti-hTNFα Ab induced by active anti-hTNFα immunization. TNF-K and IFX have similar efficacy. The co-administration of TNF-K and a short course of IFX does not result in less articular damage vs. solely TNF-K, probably due to lower anti-hTNFα Ab production. These results are relevant for future development of active anti-TNFα immunization in RA. References: Le Buanec H, Delavallee L, Bessis N, et al. TNFalpha kinoid vaccination-induced neutralizing antibodies to TNFalpha protect mice from autologous TNFalpha-driven chronic and acute inflammation. Proc Natl Acad Sci U S A 2006;103:19442-7. Delavallee L, Le Buanec H, Bessis N, et al. Early and long-lasting protection from arthritis in tumour necrosis factor alpha (TNFalpha) transgenic mice vaccinated against TNFalpha. Ann Rheum Dis 2008;67:1332-8. Delavallee L, Semerano L, Assier E, et al. Active immunization to tumor necrosis factor-alpha is effective in treating chronic established inflammatory disease: a long-term study in a transgenic model of arthritis. Arthritis Res Ther 2009;11:R195. Disclosure of Interest: L. Semerano: None Declared, J. Biton: None Declared, L. Delavallee: None Declared, E. Duvallet: None Declared, E. Assier: None Declared, N. Bessis: None Declared, E. Bernier Employee of: Neovacs S.A., O. Dhellin Employee of: Neovacs S.A., G. Grouard-Vogel Employee of: Neovacs S.A., M.-C. Boissier Grant/Research support from: Neovacs S.A., Consultant for: Neovacs S.A.